Soft tissue cephalometric standards based on NHP in a sample of Iranian adults - Mohammad Hossein Ahangar Atashi; Mozhghan Kachooei (Tabriz University of Medical Sciences, 2008)
Background and aims. This study aimed to establish soft tissue cephalometric standards in Iranian adults based on NHP, which can be used in diagnosis of orthodontic and orthognathic patients. Materials and methods. A group of 46 individuals (24 males and 22 females) with normal occlusion and proportional facial profile were chosen from a large group of dental students. For the all of the chosen sample, lateral cephalograms were obtained with head oriented in natural position. On the basis of the true horizontal and true vertical lines, the standard values of 19 soft tissue measurements were determined using McNamara, Burstone and Viazis methods. Results. In this study, the mean value of SN deviation to true horizontal line was 6.6°. Comparison between two genders showed that females have more obtuse nasolabial angle and thinner soft tissue chin than males (P < 0.05). Linear measurements showed that the overall size of males was more than females (P < 0.05). Conclusion. Cephalometric norms based on NHP were found to be more reliable in orthognathic patients.